2008
DOI: 10.1111/j.1530-0277.2008.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Acute Alcohol‐Induced Behavioral Responses Among Zebrafish Populations

Abstract: Background-With the arsenal of genetic tools available for zebrafish, this species has been successfully used to investigate the genetic aspects of human diseases from developmental disorders to cancer. Interest in the behavior and brain function of zebrafish is also increasing as CNS disorders may be modeled and studied with this species. Alcoholism and alcohol abuse are among the most devastating and costliest diseases. However, the mechanisms of these diseases are not fully understood. Zebrafish has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 34 publications
8
110
0
Order By: Relevance
“…Conditioned placed preference testing in adults has been used to identify zebrafish mutants with defects in cocaine (Darland and Dowling, 2001) or amphetamine (Webb et al, 2009) reward pathways. The effects of both acute and chronic exposure of ethanol have been extensively studied in adult locomotion (Gerlai et al, 2000(Gerlai et al, , 2008, reward (Kily et al, 2008), tolerance (Dlugos and Rabin, 2003;Blaser et al, 2010;Dlugos et al, 2011), withdrawal Cachat et al, 2010), aggression (Gerlai et al, 2000), and anxiety tests (Gerlai et al, 2006;Fernandes and Gerlai, 2009;Sackerman et al, 2010;Wong et al, 2010;Mathur and Guo, 2011;Maximino et al, 2011). Anxiolytics, including nicotine (Levin et al, 2007;Bencan and Levin, 2008), buspirone, diazepam, and fluoxetine (Bencan et al, 2009;Maximino et al, 2011), and anxiogenics such as caffeine (Egan et al, 2009) alter adult zebrafish anxiety-related behavioral responses as assessed by either a novel tank or light/dark preference paradigms.…”
Section: Probing Zebrafish Behavior With Small Moleculesmentioning
confidence: 98%
See 1 more Smart Citation
“…Conditioned placed preference testing in adults has been used to identify zebrafish mutants with defects in cocaine (Darland and Dowling, 2001) or amphetamine (Webb et al, 2009) reward pathways. The effects of both acute and chronic exposure of ethanol have been extensively studied in adult locomotion (Gerlai et al, 2000(Gerlai et al, , 2008, reward (Kily et al, 2008), tolerance (Dlugos and Rabin, 2003;Blaser et al, 2010;Dlugos et al, 2011), withdrawal Cachat et al, 2010), aggression (Gerlai et al, 2000), and anxiety tests (Gerlai et al, 2006;Fernandes and Gerlai, 2009;Sackerman et al, 2010;Wong et al, 2010;Mathur and Guo, 2011;Maximino et al, 2011). Anxiolytics, including nicotine (Levin et al, 2007;Bencan and Levin, 2008), buspirone, diazepam, and fluoxetine (Bencan et al, 2009;Maximino et al, 2011), and anxiogenics such as caffeine (Egan et al, 2009) alter adult zebrafish anxiety-related behavioral responses as assessed by either a novel tank or light/dark preference paradigms.…”
Section: Probing Zebrafish Behavior With Small Moleculesmentioning
confidence: 98%
“…Recent experiments in both larval and adult zebrafish have tested the behavioral effects of psychotropic compounds, including drugs of abuse (Gerlai et al, 2000;Darland and Dowling, 2001;Bilotta et al, 2002;Dlugos and Rabin, 2003;Lockwood et al, 2004;Gerlai et al, 2006;Lau et al, 2006;Gerlai et al, 2008;Kily et al, 2008;Lopez-Patino et al, 2008a,b;Egan et al, 2009;Fernandes and Gerlai, 2009;Gerlai et al, 2009;MacPhail et al, 2009;Webb et al, 2009;Blaser et al, 2010;Cachat et al, 2010;Irons et al, 2010;Sackerman et al, 2010;Wong et al, 2010;Dlugos et al, 2011;Mathur and Guo, 2011;Maximino et al, 2011), anxiolytics and anxiogenics (Levin et al, 2007;Bencan and Levin, 2008;Bencan et al, 2009;Egan et al, 2009;Lau et al, 2011;Maximino et al, 2011), anti-psychotics (Giacomini et al, 2006;Boehmler et al, 2007), hallucinogens (Swain et al, 2004;Blank et al, 2009;Grossman et al, 2010;Seibt et al, 2010), and sedatives (Zhdanova et al, 2001;Ruuskanen et al, 2005;Renier et al, 2007). Conditioned placed preference testing in adults has been used to identify zeb...…”
Section: Probing Zebrafish Behavior With Small Moleculesmentioning
confidence: 99%
“…Work in different adult zebrafish backgrounds (wild-type AB, wild-type long fin, wild-type short fin, or Leopard danio) demonstrated that the backgrounds exhibited different sensitivities to ethanol, while tissue levels of ethanol were consistent across the backgrounds. [34][35][36][37] In addition, the outbred 5D background was also sensitive to ethanol and this could be phenocopied by knockdown of two different microRNAs. 38 Thus, it appears that the wide range of genetic and transgenic resources available for zebrafish researchers will be readily and easily applicable to studies of FASD.…”
Section: Models Of Fasd: Return Of the Fishmentioning
confidence: 99%
“…[1][2][3] Zebrafish (Danio rerio) are rapidly emerging as a useful species for studying normal or pathological behaviors [4][5][6][7][8][9][10] and modeling complex brain disorders [11][12][13][14][15][16][17] (Table 1). The zebrafish genome is fully characterized, and their physiology and neuroanatomy parallel those of humans.…”
mentioning
confidence: 99%